1998
DOI: 10.1090/s0002-9947-98-02152-7
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of random walks on the circle generated by an irrational rotation

Abstract: Abstract. Fix α ∈ [0, 1). Consider the random walk on the circle S 1 which proceeds by repeatedly rotating points forward or backward, with probability , by an angle 2πα. This paper analyzes the rate of convergence of this walk to the uniform distribution under "discrepancy" distance. The rate depends on the continued fraction properties of the number ξ = 2α. We obtain bounds for rates when ξ is any irrational, and a sharp rate when ξ is a quadratic irrational. In that case the discrepancy falls as k − 1 2 (up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 16 publications
(15 reference statements)
2
26
0
Order By: Relevance
“…N (S k α) is the empirical analogue of ψ α (k). The order of magnitude of ψ α (k) was investigated by Schatte [20], Diaconis [12], Su [24], Hensley and Su [15]; improving their results, in [3] we showed that…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…N (S k α) is the empirical analogue of ψ α (k). The order of magnitude of ψ α (k) was investigated by Schatte [20], Diaconis [12], Su [24], Hensley and Su [15]; improving their results, in [3] we showed that…”
Section: Introductionmentioning
confidence: 88%
“…Further, M ℓ = 2 n + m ℓ 2 ℓ for some integer 0 ≤ m ℓ < 2 n−ℓ . Applying (24) on the interval [1, 2 n ] with H = n/2 and on the intervals [M ℓ + 1, M ℓ + 2 ℓ−1 ] for all n/2 ≤ ℓ ≤ n such that β ℓ−1 = 1 with the choice H = 2 ℓ/2 , we get that…”
Section: Proof For Anymentioning
confidence: 99%
“…It is clear that if ω's coordinates are well approximable by rationals, the same goes for the increments of the random walk, hence it is likely to come back closer to 0 faster. The study of random walks on a group started on finite arithmetic groups with the works of Diaconis, Saloff-Coste, Rosenthal, Porod, (see references in [24]) and results for such irrational random walks in the continuous settings were then achieved by Diaconis [8], and finally Su [24], who gave the optimal speed of convergence of the law of U n in an appropriate distance. Then Prescott and Su [22] extended the study in higher dimensional tori.…”
Section: Diophantine Random Walk On the Torusmentioning
confidence: 99%
“…According to the Central Limit Theorem, the law of the renormalised sum n −1/2 U n weakly converges to a Gaussian measure (see also Lemma 19 for precise estimates), and the law µ n of U n is known to converge to Lebesgue measure on [0, 1[ d [24]. But it seems that if we zoom in further on this convergence, it becomes very irregular.…”
Section: Irrational Random Walksmentioning
confidence: 99%
“…We give an example at the conclusion of this paper. See [9] and [10] for further work in this direction.…”
Section: Introductionmentioning
confidence: 99%